Pengembangan Bahan Ajar Video Animasi Berbasis Pendidikan Karakter pada Materi Sistem Persamaan Linier - Akhmad Yusup Efendi; Adisel Adisel; Fatrima Santri Syafri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the validity of the development and practicality of using animated video teaching materials based on character education for class VIII SMP/MTs on linear equation systems. This research is a research and development research and development (R & D) using a 4D model consisting of 4 stages, namely, Define, Design, Develop, Disseminate. Product trials were carried out in small groups of 14 students of class VIII and mathematics teachers. The results of the study where at the validation stage consisted of 4 validation people, namely 1 media expert, 1 character education value expert and 2 material experts with an average validation percentage of 82.94% with the